2012
DOI: 10.1016/j.lfs.2012.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous testosterone increases leukocyte–endothelial cell interaction in spontaneously hypertensive rats

Abstract: The findings of the present study demonstrate the critical role of endogenous testosterone mediating the effects of hypertension increasing leukocyte-endothelial cell interaction. Increased expression of cell adhesion molecules contribute to the effects of endogenous testosterone promoting increased leukocyte rolling and adhesion in SHRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…Previous reports from our group showed that testosterone does not alter venular diameter, blood flow velocity, shear rate and leucocyte velocity in the vascular bed studied in the present study (mesentery bed) [13], making unlikely the possibility that changes in venular parameters or leucocyte velocity are involved in the effects of testosterone on leucocytes migration. The fact that this effect could be observed only 24 h after testosterone administration together with the finding that flutamide blocks testosterone-induced leucocyte migration indicates that this effect occurs via genomic pathways, probably by indirect mechanisms.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Previous reports from our group showed that testosterone does not alter venular diameter, blood flow velocity, shear rate and leucocyte velocity in the vascular bed studied in the present study (mesentery bed) [13], making unlikely the possibility that changes in venular parameters or leucocyte velocity are involved in the effects of testosterone on leucocytes migration. The fact that this effect could be observed only 24 h after testosterone administration together with the finding that flutamide blocks testosterone-induced leucocyte migration indicates that this effect occurs via genomic pathways, probably by indirect mechanisms.…”
Section: Discussioncontrasting
confidence: 63%
“…Previous work from our group reported that endogenous testosterone can partly modulate early leucocyte-endothelial cell interactions in SHR [13]. Castrated SHR had lower numbers of rolling leucocytes when compared with non-castrated animals.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In addition, testosterone is a potential neuroprotective factor against the inflammation associated with neurodegenerative disorders, such as Alzheimer’s disease ( 66 ) and multiple sclerosis ( 67 ). However, this literature is confounded by mixed results, with studies showing either no ( 60 ) or a positive correlation of testosterone levels and inflammation markers ( 68 ). As well as testosterone, estrogens have also been depicted as neuroprotective and/or anti-inflammatory agents.…”
Section: Neuroinflammation and Steroidal Hormonesmentioning
confidence: 99%
“…The effects of testosterone on blood pressure regulation have been documented in animals. In hypertensive rats, the levels of testosterone correlate with the mean arterial pressure (MAP) (10,15,23,27,37). However, in some studies, testosterone was found to have no effect on the blood pressure (8,17).…”
Section: Introductionmentioning
confidence: 99%